Empowering elementary students’ higher-order thinking and creativity: the role of a problem-solving learning model with mentimeter integration in social sciences - Leny Julia Lingga; Siti Quratul Ain; Muhamad Nukman; Chantika Resdayanti; Rizqi Fajar Adi Putra (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
The present study explores the role of problem-solving learning models integrated with Mentimeter media in empowering higher-order thinking skills (HOTS) and creativity in social sciences learning at the elementary school level. A quasi-experimental, non-equivalent control-group design was used, involving two classes purposively selected. A total of 70 students were enrolled, 34 in the experimental class and 36 in the control class. Data were collected using essay tests that measured students' HOTS and creativity, then analysed using MANOVA after meeting the assumptions of normality and homogeneity. The results yielded a significant difference between the experimental class, taught using the problem-solving model with Mentimeter integration, and the control class, taught using the conventional teaching model, both in HOTS (p < 0.001) and in creativity (p < 0.001). These findings confirm the importance of combining problem-solving pedagogy with interactive technology tools in empowering elementary school students' cognitive and creative skills in social sciences learning.